Patient experiences receiving rehabilitation care via telehealth: Identifying opportunities for remote care - Goldman, Jennifer G.; Merkitch, Douglas; Brewington, David; Peirce, Hannah; Rho, Monica; Jayabalan, Prakash; Curran, Jessica; Brennan, Kimberly (Frontiers in Rehabilitation Sciences, 2023)
Use of telehealth has grown substantially in recent times due to the COVID-19 pandemic. Remote care services may greatly benefit patients with disabilities; chronic conditions; and neurological, musculoskeletal, and pain disorders, thereby allowing continuity of rehabilitation care, reducing barriers such as transportation, and minimizing COVID-19 exposure. In March 2020, our rehabilitation hospital, Shirley Ryan AbilityLab, launched a HIPAA-compliant telemedicine program for outpatient and day rehabilitation clinics and telerehabilitation therapy programs. The objective of this study was to examine patients’ experiences and satisfaction with telemedicine in the rehabilitation physician practice, including novel virtual multidisciplinary evaluations. The present study examines survey data collected from 157 patients receiving telemedicine services at Shirley Ryan AbilityLab from December 2020-August 2021. Respondents were 61.8% female, predominantly White (82.2%) with ages ranging across the lifespan (69.4% over age 50 years). Diagnostic categories of the respondents included: musculoskeletal conditions 28%, chronic pain 22.3%, localized pain 10.2%, neurological conditions 26.8%, and Parkinson’s and movement disorders 12.7%. Survey responses indicate that the telemedicine experiences were positive and well received. The majority of participants found these services easy to use, effective, and safe, and were overall satisfied with the attention and care they received from the providers— even for those who had not previously used telehealth. Respondents identified a variety of benefits, including alleviating financial and travel-related burdens. There were no significant differences in telehealth experiences or satisfaction across the different clinical diagnostic groups. Respondents viewed the integrated physician and rehabilitation therapist telehealth multidisciplinary model favorably, citing positive feedback regarding receiving multiple perspectives and recommendations, feeling like an integrated member of their healthcare team, and having a comprehensive, holistic team approach along with effective communication. These findings support that telemedicine can provide an effective care model in physiatry (physical medicine and rehabilitation) clinics, across different neurological, musculoskeletal, and pain conditions and in multidisciplinary team care settings. The insights provided by the present study expand our understanding of patient experiences with remote care frameworks for rehabilitation care, while controlling for institutional variation, and ultimately will help provide guidance regarding longer term integration of telemedicine in physiatry and multidisciplinary care models.